Efeito da dificuldade do emparelhamento com o modelo sobre diferentes topografias do relato verbal - Machado, Juliana Santana Reina (2009)
The purpose of the present study was to investigate the topography response of report own behavior on a Delayed Matching to Sample (DMTS) response that involves the selection of a stimulus and response that involves the construction of the stimulus that was selected during the DMTS and how it affects the accuracy of report and vice-verse and verify if the difficulty of DMTS affects the report manipulating the number of sample stimulus. Eight undergraduate students were subjects of the research. The procedure consisted of a Delayed Matching to Sample (DMTS) task, the report target behavior, followed by three report tasks: 1) Report by Selection Which one have you chosen? in which the subject should indicate the comparison stimuli he had chosen on the DMTS task, 2) Report by Constructed-Response Construct the figure that you have chosen! and 3) Report about the gain on the target task. In which the subject could say YES , NO or DON T KNOW . The result analysis showed that reports by selection were more accurate and CRMTS reports were less accurate. The manipulation of the number of sample stimulus showed that for the majority of the subjects, when the report was by selection accuracy tended to decrease as the number of elements increased. The curve of report of selection accompanies the DMTS curve. The results about the report about gain were similar with the report by selection. The performance of subjects on report constructed-response was different for all subjects except for three subjects the accuracy of report decrease as the number of stimulus increased